(untitled) (Applied Biological Research, 2018)
In present study, twenty-six landraces of wheat collected from different parts of Uttarakhand (India) were tested for stripe rust resistance. Initially, field resistance test was carried out at two locations, namely Hawalbagh and Dalang-Maidan (India), during 2013-14 and 2014-15 under natural conditions. The landraces were also tested against 3 pathotypes of stripe rust pathogen (110S119, 46S119 and 78S84) at seedling and adult plant stage under controlled conditions. In field, 13 landraces were found highly resistant, of which 8 were immune. The remaining 13 landraces showed varying levels of partial resistance and expressed significant genotype x environment interactions. Of the 26 landraces, only one landrace (VHC 6285) was immune against all the three pathotypes both at seedling and adult plant stages. Five landraces (VHC(BD)2, VAH-CW 3166, VRB-CW 2106, VHC 6178 and VHC 6185) showed seedling resistance against 78S84, and adult plant resistance (APR) against 110S119 and 46S119. Some landraces showed both seedling and adult plant resistance against 46S119 and 78S84. Thus, apart from reporting new sources of resistance against existing pathotypes, the current study seems to be first to report resistance sources (both seedling and APR) against new pathotype 110S119.